If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2w + 2(2w + -40) = 220 Reorder the terms: 2w + 2(-40 + 2w) = 220 2w + (-40 * 2 + 2w * 2) = 220 2w + (-80 + 4w) = 220 Reorder the terms: -80 + 2w + 4w = 220 Combine like terms: 2w + 4w = 6w -80 + 6w = 220 Solving -80 + 6w = 220 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '80' to each side of the equation. -80 + 80 + 6w = 220 + 80 Combine like terms: -80 + 80 = 0 0 + 6w = 220 + 80 6w = 220 + 80 Combine like terms: 220 + 80 = 300 6w = 300 Divide each side by '6'. w = 50 Simplifying w = 50
| 121m^2-49=0 | | -3-9y=-25 | | 1/2x-8=16 | | 10=5(m-2) | | Y-7=-14(x-9) | | 3c-b/c=a | | x-9y=-7 | | s/2-8=6 | | 2x-4=-3x-6 | | 211-6x=30x+19 | | 35-6x=3x+20 | | 3k/5+44=12k/2+58 | | 76-5x=40x+16 | | 9-0.5=1.5 | | 2(3b-2)=4b | | -7x/12=-1/6 | | A1B1/C1=A2B2/C2 | | 6x+4=-10 | | 6(q-4)=64 | | 4x^2-9x+9=3x+4 | | 2/5(5x-15)=4 | | f(x)=x^3+16x^2-19x-10 | | r-(-1.2)=7.3 | | 5m+6m+8m-5= | | 6(4-2e)-3(5+3e)= | | b+5b=42 | | 54/3^2*6(6-3) | | 13c-52= | | 6x+33=16x+3 | | 4r-1whenr=9 | | 4.6x-12.1=10.9 | | 8r^2=18+18r |